Pengaruh Labelisasi Halal dan Harga Terhadap Keputusan Pembelian: Studi Pada Produk Susu Sapi Merek Tharwa - Ramadhani, Nurul; Herman; Febrina Hambalah (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2023)
This research was conducted to find out how much influence Halal Labeling and Prices have on Purchasing Decisions for Tharwa Brand Cow's Milk products. This research was conducted using quantitative methods. This research was conducted in Surabaya with the criteria of respondents being all buyers of Tharwa Cow Milk. The sampling technique was carried out using non-probability sampling and accidental sampling techniques with a sample of 96 respondents, and data analysis using multiple linear regression analysis with the help of SPSS (Statistical Program for Social Science) Version 25.0. The results of this study can be concluded that: 1) halal labeling has no significant effect on purchasing decisions; 2) price has a significant effect on purchasing decisions; 3) Halal labeling and price together have a significant effect on product purchasing decisions on Cow's Milk